Pola Fungsi Kalimat pada Novel “9 dari Nadira” Karya Leila S. Chudori sebagai Sumber Pembelajaran dalam Mengembangkan Pemahaman Literasi Siswa Kelas X SMA - Okti Nurdianti Akmah; Astri Rivalianti; I’anatul Khofifah; Moh. Ilman Akbar Al Izaaki; Sakna Cahyani; Asep Purwo Yudi Utomo; Ludfil Khakim (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
Understanding literacy and linguistics in Indonesia, especially through novel reading, plays an important role in honing students' cognitive skills, such as critical and creative thinking. Syntax as part of linguistic studies, helps students understand language structures that support effective communication and deeper literary appreciation. This study aims to understand the structure and function of active and passive sentences in Indonesian focusing on the types of active and passive sentences and the role of sentence elements in shaping meaning. This study uses methodological and theoretical approaches with qualitative and syntactic descriptive methods to analyze the pattern of sentence function in the novel "9 of Nadira" by Leila S. Chudori. The research process involves data collection, classification, analysis, and presentation of data with listen, record, and bill techniques. The results showed that the sentence function pattern in the novel "9 of Nadira" by Leila S. Chudori uses different sentence patterns in each active and passive voice. Transitive and bitransitive active sentences have additional objects and complements, while intransitive sentences do not, and only sentences with objects can be changed to passive by undergoing changes in their predicates. This research has the benefit of providing a deeper understanding of the structure and function of active and passive sentences in Indonesian.